Impact of local anesthetics on epigenetics in cancer - Bezu, Lucillia; Kepp, Oliver; Kroemer, Guido (Frontiers in Oncology, 2022)
Defective silencing of tumor suppressor genes through epigenetic alterations contributes to oncogenesis by perturbing cell cycle regulation, DNA repair or cell death mechanisms. Reversal of such epigenetic changes including DNA hypermethylation provides a promising anticancer strategy. Until now, the nucleoside derivatives 5-azacytidine and decitabine are the sole DNA methyltransferase (DNMT) inhibitors approved by the FDA for the treatment of specific hematological cancers. Nevertheless, due to their nucleoside structure, these inhibitors directly incorporate into DNA, which leads to severe side effects and compromises genomic stability. Much emphasis has been placed on the development of less toxic epigenetic modifiers. Recently, several preclinical studies demonstrated the potent epigenetic effects of local anesthetics, which are routinely used during primary tumor resection to relief surgical pain. These non-nucleoside molecules inhibit DNMT activity, affect the expression of micro-RNAs and repress histone acetylation, thus exerting cytotoxic effects on malignant cells. The in-depth mechanistic comprehension of these epigenetic effects might promote the use of local anesthetics as anticancer drugs.